Analisa Gap Ekspektasi dan Kepuasan Wisatawan Mancanegara di Kota Manado sebagai Destinasi Wisata - Samehe, Januar valentino (Universitas Sam Ratulangi, 2019)
The research is aimed at identifying the gap between tourist’s expectation and satisfaction of Manado as tourism destination. The population of the research is international travellers with accidental sampling and analysed with gap analysis. The study shows that there is a gap between expectation and satisfaction experienced by international visitors in terms of tourism attractions, tourism facilities and priceKeywords: Gap, Expectation, Satisfaction, Tourism Attractions, Tourism Facilities, Price